Efficient Institutions and Effective Deterrence: On Timing and Uncertainty of Formal Sanctions - Johannes Buckenmaier; Eugen Dimant; Ann-Christin Posten; Ulrich Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2020)
Economic theory suggests that the deterrence of deviant behavior is driven by a combination of severity and certainty of punishment. This paper presents the first controlled experiment to study a third important factor that has been mainly overlooked: the swiftness of formal sanctions. We consider two dimensions: the timing at which the uncertainty about whether one will be punished is dissolved and the timing at which the punishment is actually imposed, as well as the combination thereof. By varying these dimensions of delay systematically, we find a surprising non-monotonic relation with deterrence: either no delay (immediate resolution and immediate punishment) or maximum delay (both resolution and punishment as much as possible delayed) turn out equally effective at deterring deviant behavior and recidivism in our context. Our results yield implications for the design of institutional policies aimed at mitigating misconduct and reducing recidivism.
Keywords: C91; D02; D81; K42; 330; deterrence; institutions; punishment; swiftness; uncertainty